Catalytically driven assembly of trisegmented metallic nanorods and polystyrene tracer particles. Issue 9 (11th February 2016) - Jewell, Erik L.; Wang, Wei; Mallouk, Thomas E.
Abstract : Trisegmented Au–Ru–Au and Ru–Au–Ru nanorods catalyze the decomposition of hydrogen peroxide, pumping fluid along their axis as "pullers" and "pushers" respectively. Abstract : Trisegmented Au–Ru–Au and Ru–Au–Ru nanorods catalyze the decomposition of hydrogen peroxide, pumping fluid along their axis as "pullers" and "pushers" respectively. Numerical simulations and experiments with passive tracer particles show that catalytically generated hydrodynamic and electrostatic forces both contribute to pairwise and collective particle assembly.